PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL PADA SISWA KELAS X SMK ST. VINCENTIUS NDONA TAHUN PELAJARAN 2018/2019 - Yohana Mbipi (Program Studi Pendidikan Matematika, 2019)
The background of this study is the low student learning outcomes in mathematics because of the lack of student involvement in the learning process. This study aims to find out: (1) student learning outcomes in the material of the Two Variable Linear Equation System through type of make a match cooperative learning; (2) Student learning activities on the Material Variable Linear Equation System (SPLDV) through the make a match type cooperative learning model. This type of research is a Class Action Research conducted in two cycles. This research was conducted at the St. Vincentius Ndona Vocational School in Ende district. Subjects in the study were 20 Electrical Grade X students. Data collection techniques used were observation, test and documentation techniques, while data analysis techniques used descriptive qualitative analysis techniques. The results of the research conducted showed an increase in student learning outcomes and student activities. In the first cycle the percentage of student activity by 60% and the second cycle by 77%, resulting in an increase of 17%. For learning outcomes, the number of students who finished in cycle I was 3 people and cycle II was 16 people. The average value obtained by students in the first cycle was 63.7 with the percentage of classical learning completeness of 35%. Whereas in the second cycle, the average value obtained by students was 81.31 with a percentage of classical learning completeness of 84.21%, resulting in an increase in student learning outcomes by 49.21%. Thus it can be concluded that the model of make a match cooperative learning can improve student learning outcomes in class X Electric Vocational School St. Vincentius Ndona in the material of the Two Variable Linear Equation System.